Media Playdough untuk Membantu Perkembangan Motorik Halus pada Anak Usia Pra Sekolah - Dea Sri suhartini; Rinrin Sugiartin; Nendah Sulistiani; Imel Puji Astuti; Sulistiarini; Reika Dhamayanti; Andan Firmansyah (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: Playdough is a modern form of clay made from a mixture of wheat flour. Playdough is easy to play and liked by children, because it can be played using hands and tools to form dough. Through this experience, children can develop eye coordination, dexterity and hand strength which can stimulate children's motoric development for writing and coloring. Objective: The purpose of this service was to present the results of play therapy using playdough in improving fine motor skills of preschoolers in Al-Islah Kindergarten. Method: This community service uses a play therapy approach involving 12 participants, assisted by writers and kindergarten teachers. Data collection was carried out by means of health counseling, observation, interviews and documentation on Al-Islah Kindergarten children in Kawali sub-district, Ciamis Regency, West Java. Result: The results of the dedication obtained a positive influence on the counseling participants, and this play therapy was enthusiastically responded to by the participants of the Al-Islah Kindergarten. This can be seen from the time the participants were active and happy to play playdough. Conclusion: The use of playdough media can help children practice motor skills with their hands, while manipulating playdough with their fingers. So that playdough games can be a good stimulation tool and are not dangerous for pre-school children.